Gelatinisation of sago starch in the presence of sucrose and sodium chloride as assessed by differential scanning calorimetry - Maaurf, A.G; Che Man, Y.B; Asbi, B.A; Junainah, A.H; Kennedy, J.F (Elsevier Science, 2001)
The inhibitory effect of sucrose and sodium chloride on sago starch gelatinisation was investigated by differential scanning calorimetry (DSC). The temperature of gelatinisation of starch in the presence of low levels of water and high levels of sucrose was found to increase in the presence of sucrose, whereas the gelatinisation enthalpy was unaffected. The gelatinisation temperature range was not as broad in the presence of sucrose as without sucrose. Furthermore, the shape of the gelatinisation endotherm was changed by the addition of sucrose. The double endotherm obtained in limited water:starch systems was changed into a single endotherm, similar to the endotherm obtained in excess water:starch systems at a higher temperature. DSC was also used to examine the effects of water and sodium chloride content on the phase transitions of sago starch. Samples were adjusted to starch:water ratios of 2:3 and 3:2 in sodium chloride concentrations of 0.0, 1.0, 2.0, 3.0, 4.0, 5.0 M. The gelatinisation temperatures of sago starch increased and then decreased as the sodium chloride concentration increased. Sodium chloride created similar effects on the endotherms in excess water content and on the first endotherm with limited water content. In the presence of sucrose and sodium chloride, gelatinisation shifted to higher temperatures, and enthalpy associated with the endothermic process decreased. The extent of temperature shift and enthalpy change was dependent on the water to starch to solutes ratios.